Enhancing Speaking Skills Through Storytelling Activities For 10th Grade Students at PKBM Al-Amanah Bekasi - Alghifari, Ichwan; Agustin, Iswandini; Sari, Tiara Dian (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This research aims to enhance the English speaking skills of tenth-grade students by applying storytelling methods at PKBM Al Amanah Bekasi. The background of this study is the low level of students' speaking skills, which is characterized by a lack of fluency, vocabulary mastery, and low confidence in expressing ideas orally. This study uses the classroom action research (CAR) method developed by Kemmis and McTaggart, which consists of two cycles, each comprising the stages of planning, implementation, observation, and reflection. Data collection techniques include observation, interviews, and speaking ability tests. The assessment instruments covered five aspects of speaking skills: fluency, pronunciation, vocabulary, grammar, and confidence. The study's results showed that students' speaking skills improved in each cycle. The average score of students increased from 57.76 in the pre-cycle to 72.16 in Cycle I, and reached 78.56 in Cycle II. The percentage of learning achievement also increased from 24% to 84%. This improvement indicates that the storytelling method is effective in helping students develop their speaking skills in a more active, confident, and communicative manner. Therefore, the application of the storytelling method can be an innovative and enjoyable learning strategy to enhance students' speaking skills.